Better Together: Mathematics and Science Pre-Service Teachers' Sensemaking about STEM - Lawson, Michael A.; Herrick, Imogen R.; Rosenberg, Joshua M. (Educational Technology ＆ Society, 2021)
While the perspectives and practices of many educational stakeholders in relation to STEM have been documented, research has yet to deeply explore pre-service teachers' (PST) understandings and how to support their sensemaking about STEM during pre-service teacher education. To address this, we used two STEM integration frameworks, focused on discipline-based practices and modeling with data, to inform the design of a STEM unit that brought together thirty secondary mathematics and science PSTs. With an eye on PSTs' development of a situated understanding of STEM, a qualitative analysis of pre/post surveys and STEM lesson sketches revealed that PSTs collectively shifted from initial views of STEM as blurred lines between subjects to a more nuanced understanding of where and how subjects cross and meet. PSTs also described STEM activities through a more plausible understanding of student and teacher actions and viewed data as a bridge to connect disciplines and the real-world. Furthermore, PSTs' descriptions of anticipated challenges to planning for and implementing STEM mirrored those of in-service teachers. We discuss these findings through the lens of sensemaking theory, highlighting shifts in the sum of PSTs' individual understandings to a more collective and situated understanding of STEM. We also discuss implications focused on the role of data in STEM activities and the affordances of secondary mathematics and science PSTs sensemaking together to about STEM.